Exploring the New Zealand Child and Youth Profile as a collaborative tool to support educational planning for children with fetal alcohol spectrum disorder : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts (Education), Massey University, Palmerston North, New Zealand - van Wyk, Joanne (Massey University, 2019)
Research indicates that students with fetal alcohol spectrum disorder (FASD) are at increased risk of poor academic performance, however, educational planning for these students is difficult due to the complex nature of their educational profile. In order to improve educational outcomes, tools are required to support improved understanding of the student’s profile along with enhancing a cross-disciplinary approach to educational planning. This study sought to investigate the use of the New Zealand Child and Youth Profile (NZCYP), a biopsychosocial framework designed to collect key information about a student from multiple perspectives, in order to facilitate cross-disciplinary educational collaboration and planning. A qualitative design was employed to explore the perceptions of two teams of participants using the NZCYP to support a student with FASD. Findings indicated several factors hindered the completion and application of the NZCYP (or Toolkit), which had a considerable impact on the teams’ perceptions of the NZCYP. Overall, the teams perceived the NZCYP’s ability to help improve understanding of the student’s profile, to support teacher/classroom practice and planning, and to enhance collaborative practice was limited. This study highlighted the importance of providing tools which are easily understood, incorporate culturally relevant information and multiple perspectives, and provide suitable training to enable teams to utilise the information in a cross-disciplinary manner.
Figures re-used with permission.
Keywords: Learning disabled children; Education; New Zealand; Fetal alcohol spectrum disorders; New Zealand Child and Youth Profile; 390499 Specialist studies in education not elsewhere classified